2002
DOI: 10.2514/2.6052
|View full text |Cite
|
Sign up to set email alerts
|

Direct Experimental Impulse Measurements for Detonations and Deflagrations

Abstract: = pendulum mass P = pressure P env = environment pressure P lip = pressure on lip at exit of tube P TS = pressure on thrust surface in detonation tube interior P 1 = initial pressure of reactants P 2 = Chapman-Jouguet pressure P 3 = pressure of burned gases behind Taylor wave p = pitch of spiral obstacles S = wetted surface area of tube's inner diameter T 1 = initial temperature of reactants t = time U CJ = Chapman-Jouguet detonation velocity V = internal volume of detonation tubē = ratio of N 2 -to-O 2 concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
66
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 13 publications
9
66
1
Order By: Relevance
“…The PDEs are classified as air-breathing PDEs [19][20][21][22] or pulse detonation rocket engines (PDREs) [23][24][25]. With a simplified PDE setup, that is, when viscosity and heat conduction are neglected and a tube-geometry combustor is fully filled with propellant at ambient pressure and a detonation wave is initiated instantaneously, a PDRE using H 2 -O 2 propellant can achieve a specific impulse of 190 sec and an air-breathing PDE using hydrogen fuel can achieve a specific impulse of 4200 sec, as achieved in experiments by Schuer et al [26], Cooper et al [27] and…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The PDEs are classified as air-breathing PDEs [19][20][21][22] or pulse detonation rocket engines (PDREs) [23][24][25]. With a simplified PDE setup, that is, when viscosity and heat conduction are neglected and a tube-geometry combustor is fully filled with propellant at ambient pressure and a detonation wave is initiated instantaneously, a PDRE using H 2 -O 2 propellant can achieve a specific impulse of 190 sec and an air-breathing PDE using hydrogen fuel can achieve a specific impulse of 4200 sec, as achieved in experiments by Schuer et al [26], Cooper et al [27] and…”
Section: Introductionmentioning
confidence: 90%
“…However, Takeuchi et al [44] reported that the specific impulse decreased when the length ratio (l DDT / l p ) between the propellant fill length, l p , and the DDT distance, l DDT , decreased. They varied the initial fill pressure of the H 2 -O 2 stoichiometric mixture and investigated the relation between the DDT distance and the specific impulse by a shingle-shot ballistic pendulum and found that the specific impulse rapidly decreased when the length ratio (l DDT / l p ) was 0.9. Cooper et al [27] also varied the nitrogen-dilution ratio of the mixture and investigated the impact of DDT distance on the specific impulse using a shingle-shot ballistic pendulum. They found that the DDT distance increased as the nitrogen-dilution ratio increased, and the specific impulse decreased compared to a theoretical value.…”
mentioning
confidence: 99%
“…2 In other studies, a weakening of bow shocks was observed when heat was added using GDP that formed between the body and the bow shock. 3 The results of these studies demonstrated the potential of the plasma technology in high-speed aerodynamics. The exact nature of plasma-shockwave interaction is not clearly understood.…”
Section: Introductionmentioning
confidence: 75%
“…The final velocity of the driven mass is determined from the conservation equations and depends on the available chemical energy of the explosive. The impulse corrections applied, measured as a percentage of the measured impulse, are less than 2.3% for Cooper et al, 3 less than 21.3% for Falempin et al, 4 less than 22.3% for Zhdan et al, 2 and less than 25.1% for Zitoun and Desbordes.…”
Section: Data For Partially Filled Tubesmentioning
confidence: 99%
See 1 more Smart Citation